Nitrogen-enriched pseudographitic anode derived from silk cocoon with tunable flexibility for microbial fuel cells. (February 2017) - Lu, Min; Qian, Yijun; Yang, Cuicui; Huang, Xiao; Li, Hai; Xie, Xiaoji; Huang, Ling; Huang, Wei
Abstract: Microbial fuel cells (MFCs), promising for converting biomass energy into electricity, have attracted much research enthusiasm. However, high performance anode materials for MFC, particularly with tunable flexibility for diverse cell configurations, are still limited. In this study, through a simple one-step carbonization of a versatile protein precursor, silk cocoon, both freestanding and flexible bioanode materials, with enriched nitrogen contents and hierarchical pores, can be easily fabricated. Importantly, the carbonized silk cocoon, as a freestanding MFC anode, and flexible carbon fiber, as a flexible MFC anode, exhibit high performance in electricity generation, yielding about 2.5-fold and 3.1-fold maximum gravimetric power density than that of MFCs with carbon cloth anode, respectively. We attribute the improved anode performance of these flexibility tunable carbon materials to their good biocompatibility, reduced electron transfer resistance and high capacitance. This study will not only offer great opportunities for the fabrication of high-performance MFC anode with varied designs and 3-dimensional architectures, but also shed light on the future development of MFC and proper utilization of the abundant "green" natural resources. Graphical abstract: Highlights: Silk cocoon is a versatile natural protein for the fabrication of pseudographitic carbon materials with tunable flexibility. Microbial fuel cells equipped with carbon materials derived from silk cocoon exhibit high anode performance. Pseudographitic carbon derived from silk cocoon features enriched nitrogen content, hierarchical pores, good biocompatibility and high capacitance.